Captivity Is Associated With Gut Mycobiome Composition in Tibetan Macaques (Macaca thibetana) - Sun, Binghua; Xia, Yingna; Garber, Paul A.; Amato, Katherine R.; Gomez, Andres; Xu, Xiaojuan; Li, Wenbo; Huang, Mingjing; Xia, Dongpo; Wang, Xi; Li, Jinhua (Frontiers in Microbiology, 2021)
Although recent studies have revealed that gut fungi may play an important functional role in animal biology and health, little is known concerning the effects of anthropogenic pressures on the gut mycobiome. Here, we examined differences of the gut mycobiome in wild and captive populations of Tibetan macaques (Macaca thibetana) targeting the fungal internal transcribed spacer (ITS) and using next generation sequencing. Our findings demonstrate that the diversity, composition, and functional guild of the Tibetan macaque gut mycobiome differ across populations living in different habitats. We found that Tibetan macaques translocated from the wild into a captive setting for a period of one year, were characterized by a reduction in fungal diversity and an increase in the abundance of potential gut fungal pathogens compared to wild individuals. Furthermore, we found that the relative abundance of two main fungal guilds of plant pathogens and ectomycorrhizal fungi were significantly lower in captive individuals compared to those living in the wild. Our results highlight that, in addition to bacteria, gut fungi vary significantly among individuals living in captive and wild settings. However, given limited data on the functional role that fungi play in the host’s gut, as well as the degree to which a host’s mycobiome is seeded from fungi in the soil or ingested during the consumption of plant and animal foods, controlled studies are needed to better understand the role of the local environment in seeding the mycobiome.